Prison law and human rights in post-communist Romania: Staff attitudes toward change - Dâmboeanu, Cristina (European journal of criminology, 2021)
Previous research has documented the crucial role that the perceptions and attitudes of prison staff play in everyday prison practice and the treatment of prisoners. The current study follows this contention in order to investigate how prison staff in Romania perceive the outcomes of the recently adopted prison law advocating the principle of humanization and the protection of prisoners’ rights. Specifically, drawing from Jacobs’ (1980) early study on the impact of the prisoners’ rights movement, the effects of the prison law on: (1) prisoners; (2) prison practice and management; and (3) prison staff are investigated from the perspective of a sample of approximately 300 staff members. Whether these perceptions vary across specific socio-demographic groups, occupational categories and groups defined by their level of job satisfaction, punitive attitudes and commitment to custodial role is also examined. We conclude by arguing that, although time is needed to thoroughly assess the prison law’s effects, surveying prison staff’s opinions and perceptions about its outcomes is nevertheless legitimate, because how staff members feel, experience and perceive these outcomes and whether the balance inclines toward the positive aspects or toward the negative ones are crucial for the success or, on the contrary, the failure of an ongoing implementation of those reforms.